A matemática por meio da estatística ajudando a entender o processo eleitoral - Melo Júnior, Humberto Vieira de (2019)
This paper aimed to study mathematics through the use of statistics to better clarify the complex electoral process in current systems. Initially, we sought a review on the statistical and graphical subjects related to the topics to be addressed, due to the need for knowledge in order to better understand the subject studied. Subsequently, the statistical formulas that are used in the current Brazilian elections were presented. In addition, work was carried out with election simulations at the Tarcísio de Jesus State School, with the purpose of studying the theme addressed in this research and reaching the target audience that is the school community of the mentioned School. Finally, exercises were performed with the proposal of alternatives for the teaching of mathematics in Basic Education.